Criança e infância nas obras de Arthur Ramos: estudos da infância no Brasil a partir de produções nacionais da década de 1930 - Francchini, Flavia (Universidade Federal de São Carlos, 2020)
This research refers to a bibliographic study developed with the purpose of presenting a cartography of childhood studies in Brazil, particularly during the 1930s, taking as reference the works of Arthur Ramos. For the analysis prioritized the main productions of the author in the decade in question: Education and Psychoanalysis (1934), the Spirit Health: Mental Health (1939), The Problem Child: Mental Health in Primary School (1939), in order to map out what are the descriptions and how the child and childhood are portrayed, analyzing specifically age relations, ethnic, racial and gender. First return to the Brazilian history, highlighting the major changes in the education sector during the late 1930s, and Arthur Ramos relationship with the main movements developed at the time in question, which aimed to prepare the population for the modernization of capitalist society. We also emphasize the life and professional career of the psychiatrist, and how consolidated the inclusion of child psychoanalysis in Brazilian education. In a second step, we present the results of an analytical literature review of contemporary studies on Arthur Ramos and his productions. Finally, critically analyze the analytical work of Arthur Ramos organized in three main lines of analysis titled: a) Psychoanalysis, Child and Education: b) Thinking Children and Childhood Brazilian, c) Strengthening the Building of a Society Forged in Myth of Racial Democracy. We conclude that the analytical work of Ramos presents key issues to think about the constitution of the debate on children, childhood and contemporary Brazilian education, start by identifying that the current problems of school failure carry a legacy of guided justifications in the educational project developed in the late 1930s also identified that the Brazilian psychoanalytic debate is concomitant racial debate, and Arthur Ramos to build the universal conception of Brazilian children, also built the concept of the ideal of whiteness in Brazil, classifying the children coming from families nonstandard he considered normal if the main problem to achieve a clean society, civilized and adapted to the capitalist system. Arthur Ramos, when considering that the child should also be studied from the anthropological conceptions considering its family and social relationships, just somehow identifying the urgent need for a sociology of childhood or childhood studies in Brazil. Exposing the course of its fundamental elements productions to think about children and childhood from a sociological perceptive, although not this your goal.
Child and childhood in the works of Arthur Ramos: childhood studies in Brazil from national productions of the 1930s
L'enfance et l'enfance dans les œuvres d'Arthur Ramos: études sur l'enfance au Brésil à partir de productions nationales des années 30
Keywords: Criança; Infância; Estudos da infância no Brasil; Arthur Ramos; Child; Childhood; Childhood studies in Brazil; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO